Secondary battery, preparation method thereof and electric device
By using copper foil composed of copper grains of different particle sizes as the negative electrode current collector, the problem of insufficient performance of the negative electrode current collector in existing secondary batteries is solved, and higher energy density and better safety are achieved.
Patent Information
- Application Number
- CN202411154807.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-21
AI Technical Summary
The negative current collector performance of existing secondary batteries is insufficient, and it cannot effectively restrict the expansion of the battery cell, resulting in fracture of the electrode piece, affecting the service life and safety of the battery.
Copper foil composed of copper grains of different particle sizes is used as the negative electrode current collector. By adjusting the number proportion and particle size distribution of copper grains, the tensile strength and elongation of breakage of copper foil are improved.
It significantly improves the energy density, capacity and safety of the secondary battery, extends the battery life, and reduces the risk of extreme pieces fracture.
Smart Images

Figure CN119852540A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and a preparation method thereof and an electrical device. Background Art
[0002] As secondary batteries are widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market has increasingly higher requirements for the energy density of secondary batteries.
[0003] Energy density can be increased by using silicon-based negative electrode active materials or increasing the amount of secondary battery active materials, but silicon-based materials have a high thermal expansion coefficient, and silicon-based batteries expand severely when heated; the volume of the battery cell increases accordingly when the amount of secondary battery active materials increases, which puts higher requirements on the performance of the negative electrode current collector. The negative electrode current collector copper foil is an important component of the secondary battery. It can restrain the expansion of the battery cell and prevent the anode of the secondary battery from breaking during use, which has a great impact on the electrical performance and safety performance of the secondary battery.
[0004] Therefore, there is an urgent need for a secondary battery with improved negative electrode current collector performance. Summary of the invention
[0005] The present application provides a secondary battery having a negative electrode current collector with improved tensile properties, which can effectively restrain the expansion problem of the battery cell, delay or reduce the fracture of the pole piece, and extend the service life of the secondary battery.
[0006] In a first aspect, the present application provides a secondary battery, the secondary battery comprising copper foil, the copper foil comprising copper grains of different particle sizes, the copper grains comprising copper grains with a particle size less than or equal to 0.5 μm and copper grains with a particle size greater than 0.5 μm, wherein the number of copper grains with a particle size less than or equal to 0.5 μm accounts for 70%-95% of the total number of copper grains, and the number of copper grains with a particle size greater than 0.5 μm accounts for 5%-30% of the total number of copper grains.
[0007] The copper foil provided in the present application has excellent tensile strength and elongation at break, and has excellent plasticity while improving mechanical strength, providing a material basis for improving the energy density, capacity and safety of secondary batteries.
[0008] In any embodiment, the copper crystal grains with a grain size greater than 0.5 μm have a grain size range of greater than 0.5 μm and less than or equal to 3 μm, which can adjust or optimize the tensile strength of the copper foil.
[0009] In any embodiment, the number of copper grains with a particle size of less than or equal to 0.5 μm accounts for 80%-95% of the total number of copper grains, which helps to further enhance the tensile strength and improve the mechanical strength of the copper foil.
[0010] In any embodiment, the number of copper grains with a particle size greater than 0.5 μm accounts for 5%-20% of the total number of copper grains, which helps to further increase the elongation at break and improve the plasticity of the copper foil.
[0011] In any embodiment, the copper foil satisfies at least one of the following conditions:
[0012] (1) The average particle size of copper grains is 0.3 μm-1.2 μm;
[0013] (2) The maximum particle size of copper grains is 1 μm-2.5 μm;
[0014] (3) The minimum particle size of copper grains is 0.1 μm-0.3 μm;
[0015] (4) The particle size of copper grains ranges from 0.8 μm to 2.5 μm.
[0016] The particle size distribution of copper grains helps to adjust the ratio of copper grains with a particle size less than or equal to 0.5 μm and copper grains with a particle size greater than 0.5 μm, thereby adjusting and improving the tensile strength and elongation at break of the copper foil, so that the copper foil has both excellent mechanical properties and plastic properties.
[0017] In any embodiment, the copper foil satisfies at least one of the following conditions:
[0018] (1) The average particle size of copper grains is 0.3 μm-0.6 μm;
[0019] (2) The maximum particle size of copper grains is 1.2 μm-2.0 μm;
[0020] (3) The minimum particle size of copper grains is 0.1 μm-0.3 μm;
[0021] (4) The particle size of copper grains ranges from 1 μm to 2 μm.
[0022] The particle size distribution of copper grains helps to further adjust the tensile strength and elongation at break of copper foil and improve the mechanical properties and plastic properties.
[0023] In any embodiment, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 600MPa-1000MPa, and / or the elongation at break of the copper foil is 4%-8%.
[0024] The copper foil has excellent tensile strength and elongation at break, good mechanical properties and plastic properties, can be applied to high energy density batteries or high expansion batteries, and helps to improve the safety of secondary batteries.
[0025] In any embodiment, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 700MPa-1000MPa, and / or the elongation at break of the copper foil is 4%-7%.
[0026] In any embodiment, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 700MPa-800MPa, and / or the elongation at break of the copper foil is 5%-6%.
[0027] The copper foil has good tensile strength, which can meet the actual demand for high-strength copper foil in the battery field to a certain extent. In addition, the copper foil also has excellent elongation at break and exhibits good plasticity, which helps to reduce the brittle defects of the copper foil and reduce the risk of copper foil breakage or slight cracks in the battery core.
[0028] In any embodiment, the hardness of the copper foil is 55HV-65HV. In any embodiment, the hardness of the copper foil is 55HV-60HV. Appropriate hardness is beneficial to the surface treatment of the copper foil and the cold pressing treatment of the secondary battery, reducing the surface damage of the copper foil and reducing the influence on the bonding performance of the negative electrode film layer and the copper foil.
[0029] In any embodiment, the thickness of the copper foil is 4 μm-10 μm. The copper foil can be thinned without affecting the strength, which is helpful for lightweight design of batteries and further improves energy density or specific capacity.
[0030] In any embodiment, the secondary battery also includes a negative electrode film layer located on at least one side of the copper foil, and the negative electrode active material in the negative electrode film layer includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material and lithium titanate. The secondary battery can be applicable to a variety of different battery negative electrode systems and has a wide range of applications.
[0031] In any embodiment, the negative electrode active material includes a silicon-based material, and the silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. A secondary battery using a silicon-based material as a negative electrode active material has a higher energy density, and at the same time, the copper foil in the secondary battery can well restrain the volume expansion of the negative electrode during the battery cycle.
[0032] A second aspect of the present application provides a method for preparing a secondary battery, including preparing copper foil by electroplating, wherein the electroplating method includes applying a pulse current to a plating solution to reduce and deposit copper ions in the plating solution to form copper foil, wherein the peak value of the pulse current is 40000A-100000A, the valley value of the pulse current is 100A-20000A, and the current variation period is 50ms-5000ms.
[0033] Compared with the calendering method, the electroplating process is mature and simple, with low equipment requirements. The prepared copper foil has excellent tensile strength and elongation at break, and has both excellent mechanical strength and good plasticity.
[0034] In any embodiment, the electroplating method satisfies one or more of the following conditions:
[0035] (1) The peak value of the pulse current is 40000A-80000A;
[0036] (2) The valley value of the pulse current is 1000A-10000A;
[0037] (3) The pulse current has a variation period of 500ms-5000ms;
[0038] (4) The distance between the cathode electrode and the anode electrode is 8 mm to 20 mm;
[0039] (5) The temperature of electroplating deposition is 45°C-60°C;
[0040] (6) The cathode roller speed is 2m / min-5m / min.
[0041] In any embodiment, the electroplating method satisfies one or more of the following conditions:
[0042] (1) The peak value of the pulse current is 50000A-70000A;
[0043] (2) The valley value of the pulse current is 2000A-5500A;
[0044] (3) The pulse current has a variation period of 2000ms-4000ms;
[0045] (4) The distance between the cathode electrode and the anode electrode is 8mm-12mm;
[0046] (5) The temperature of electroplating deposition is 50℃-60℃;
[0047] (6) The cathode roller speed is 2m / min-3m / min.
[0048] Compared with direct current deposition, applying pulse current to the plating solution can cause copper ions to be reduced and deposited under high current conditions to form fine grains with smaller particle sizes, and to form larger grains (e.g., columnar crystals) under low current conditions. By adjusting the current size and the change cycle, the formation and growth of copper ion nuclei can be adjusted, thereby adjusting the size and morphology of the grains, as well as adjusting the number ratio of copper grains with a particle size of less than or equal to 0.5μm and copper grains with a particle size of greater than 0.5μm, and improving the tensile strength and elongation at break of the copper foil.
[0049] In any embodiment, the pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current. In any embodiment, the pulse current includes a sine wave pulse current. The continuous and periodic changes of the sine wave pulse current are conducive to the continuous and variable growth of the grains.
[0050] In any embodiment, the electroplating solution includes a leveler, a wetting agent and a brightener, the leveler includes one or more of collagen and sodium saccharin; the wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; the brightener includes sodium polydisulfide dipropane sulfonate.
[0051] Leveling agents can improve the flatness of copper foil, wetting agents can improve the wettability of the plating solution and the substrate, increase the nucleation rate of copper foil, and reduce the average particle size of the grains in the copper foil. Brighteners can make the grain size of copper foil smaller, reduce the surface roughness of copper foil, and improve the smoothness of the surface.
[0052] In any embodiment, the electroplating solution includes: collagen with a concentration of 60 mg / L to 300 mg / L, saccharin sodium with a concentration of 0.5 g / L-10 g / L, polyethylene glycol with a concentration of 50 mg / L to 200 mg / L, hydroxyethyl cellulose with a concentration of 30 mg / L to 200 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 500 mg / L to 2000 mg / L, and chloride ions (calculated as chlorine atoms) with a concentration of 20 mg / L to 80 mg / L.
[0053] In any embodiment, the electroplating solution includes: the electroplating solution includes: collagen with a concentration of 80 mg / L to 150 mg / L, saccharin sodium with a concentration of 0.5 g / L-4 g / L, polyethylene glycol with a concentration of 60 mg / L to 150 mg / L, hydroxyethyl cellulose with a concentration of 50 mg / L to 150 mg / L, sodium polydisulfide propane sulfonate with a concentration of 500 mg / L to 1000 mg / L, and chloride ions with a concentration of 40 mg / L to 80 mg / L.
[0054] Collagen and sodium saccharin in the plating solution help to improve the surface pits and protrusions of the copper foil and improve the flatness of the copper foil. Hydroxyethyl cellulose and polyethylene glycol are beneficial to reduce the difference in the thickness direction of the copper foil and improve the uniformity of the copper foil. Sodium polydisulfide dipropane sulfonate can increase the electrochemical reduction rate of copper ions and adjust the grain size. The resulting copper foil is bright and smooth, and the number of copper grains with a particle size less than or equal to 0.5μm and the number of copper grains with a particle size greater than 0.5μm are appropriate, and it has good tensile strength and elongation at break.
[0055] In any embodiment, the pH of the electroplating solution is 2.5-4.5 to facilitate the reduction of copper ions.
[0056] A third aspect of the present application provides an electrical device, comprising the secondary battery of the first aspect of the present application or the secondary battery prepared by the method of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0058] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0059] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0060] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0061] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0062] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0063] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0064] Figure 7 The inverse pole figure distribution diagram of the cross section of the copper foil of Example 1 of the present application after electron backscatter diffraction (EBSD) testing is shown.
[0065] Figure 8 The tensile curve of the copper foil of Example 1 of the present application is shown.
[0066] Fig. 9 The particle size distribution diagram of the copper foil cross section of Example 1 of the present application obtained by EBSD diffraction test is shown.
[0067] Fig.10 The inverse pole figure distribution diagram of the copper foil cross section of Example 2 of the present application after EBSD testing is shown.
[0068] Fig.11 The tensile curve of the copper foil of Example 2 of the present application is shown.
[0069] Fig.12 The particle size distribution diagram of the copper foil cross section of Example 2 of the present application obtained by EBSD diffraction test is shown.
[0070] Fig.13 The inverse pole figure distribution diagram of the copper foil cross section of Example 3 of the present application after EBSD testing is shown.
[0071] Fig.14 The tensile curve of the copper foil of Example 3 of the present application is shown.
[0072] Fig.15 The particle size distribution diagram of the copper foil cross section of Example 3 of the present application obtained by EBSD diffraction test is shown.
[0073] Fig.16 The tensile curve of the copper foil of Example 3 of the present application is shown.
[0074] Fig.17 The inverse pole figure distribution diagram of the copper foil cross section of Comparative Example 2 of the present application after EBSD testing is shown.
[0075] Fig.18 The tensile curve of the copper foil of Comparative Example 2 of the present application is shown
[0076] Fig.19 The particle size distribution diagram of the copper foil cross section of Comparative Example 2 of the present application obtained by EBSD diffraction test is shown.
[0077] Description of reference numerals:
[0078] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0079] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0080] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0081] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0082] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0083] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0084] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0085] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0086] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charge and discharge process, active ions (for example, lithium ions, sodium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through. The negative electrode sheet includes a negative current collector, which is used to carry the electrode active material and collect the output current, and can also restrain the expansion of the battery cell to prevent the anode from breaking during the cycle.
[0087] Increasing the amount of active materials can increase the energy density or capacity of secondary batteries, but it will lead to an increase in the volume of the battery cell; using silicon-based negative electrode materials can also increase the energy density or capacity of secondary batteries, but silicon-based negative electrode materials have high expansibility, resulting in severe expansion and contraction of the pole piece volume during the cycle. This can easily lead to the breakage or slight cracking of the copper foil in the battery cell, causing a short circuit in the battery, which seriously affects the safety of the secondary battery. At present, the tensile strength of the conventional negative electrode current collector copper foil is usually 200MPa-500MPa, which cannot meet the high energy density or high capacity requirements of the new generation of secondary batteries. Refining copper grains can strengthen the material strength, but it can aggravate the brittle defects of copper foil and increase the risk of copper foil breakage or slight cracking. How to improve the strength of copper foil while taking into account good plasticity is a problem that needs to be solved urgently.
[0088] [Secondary battery]
[0089] Based on this, the present application provides a secondary battery, the secondary battery includes a negative electrode current collector, the negative electrode current collector includes copper foil, the copper foil includes copper grains of different particle sizes, the copper grains include copper grains with a particle size less than or equal to 0.5 μm and copper grains with a particle size greater than 0.5 μm, wherein the number of copper grains with a particle size less than or equal to 0.5 μm accounts for 70%-95% of the total number of copper grains, and the number of copper grains with a particle size greater than 0.5 μm accounts for 5%-30% of the total number of copper grains.
[0090] Copper grains with a particle size of more than 0.5 μm tend to appear as columnar grains or quasi-columnar grains, also referred to as "large grains" herein, and copper grains with a particle size of less than or equal to 0.5 μm appear as fine grains that are close to granular, and a fine grain region is formed around the columnar grains. Therefore, in the present application, the copper foil substrate forms a grain morphology that is mainly composed of fine grains and a mixed distribution of large grains, and has a heterogeneous grain morphology in which a small amount of large grains are doped in fine grains. The main reason for the difference in the heterogeneous morphology of large and small grains is the regulation of the grain size during the foil production process. Specifically as an embodiment, the copper foil can control the grain size by adjusting the change in the current during the foil production process. When the current is reduced, the grains tend to form larger grains, and when the current is increased, the grains tend to form smaller grains.
[0091] Copper grains with a particle size of 0.5 μm or less help improve the tensile strength of copper foil and improve the mechanical properties; copper grains with a particle size greater than 0.5 μm help improve the elongation at break and improve the plasticity of copper foil. The proportion of copper grains with a particle size of 0.5 μm or less and copper grains with a particle size greater than 0.5 μm in the copper grains can have different degrees of influence on the mechanical properties and plasticity of copper foil, making the copper foil comprehensively show different degrees of excellent mechanical properties and plasticity. In the copper foil provided by the present application, the proportion of copper grains with a particle size less than or equal to 0.5 μm in the total number of copper grains is 70%-95%, which can significantly improve the tensile strength of the copper foil. At the same time, the proportion of copper grains with a particle size greater than 0.5 μm in the total number of copper grains is 5%-30%, which can make the copper foil have a good elongation at break. The copper foil has both excellent mechanical properties and plasticity, which can reduce the risk of copper foil breaking or cracking in high energy density battery systems or high expansion system batteries, and provide a material basis for improving the energy density and safety of secondary batteries.
[0092] Without wishing to be bound by any theory, the work hardening ability of large grains and fine grains is quite different. The heterogeneous grain morphology of a small amount of large grains doped in fine grains makes the strain zoning in the early stage of plastic deformation of copper foil more obvious. This may be due to the moderate doping of large grains compared to all fine grains, the former produces a higher density of geometrically necessary dislocations during the inhomogeneous plastic deformation process. In the process of inhomogeneous plastic deformation, the copper foil can cause the crystal plane of the grain to bend and produce dislocations. This dislocation is called geometrically necessary dislocation (GND). Geometrically necessary dislocation can coordinate the plastic strain caused by deformation and maintain material continuity, which helps to reduce the occurrence of concentrated stress during the deformation of copper foil, so that the copper foil shows a stronger ability to suppress strain localization, and the plasticity of the copper foil is improved. In addition, in the copper foil crystal, the contact interface between grains is called the grain boundary. It can be understood that in the same area, the smaller the grain size, the higher the total grain boundary area, the higher the grain boundary stress that the copper foil needs to overcome during the deformation process, and the higher the resistance to deformation of the copper foil, that is, the higher the mechanical strength. At the same time, the higher density of geometric dislocations generated by the copper foil during the deformation process helps to reduce concentrated stress and improve mechanical strength.
[0093] In some embodiments, the number of copper grains with a particle size less than or equal to 0.5 μm accounts for 75%-95%, 80%-95%, 85%-95%, 83%-93%, 85%-93% or 87%-93% of the total number of copper grains, which helps to further improve the tensile strength and optimize the mechanical properties of the copper foil.
[0094] In some embodiments, the number of copper grains with a particle size of less than or equal to 0.5 μm accounts for 75%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, or a range between any two of the above values or any value within the range.
[0095] Herein, the particle size range of the copper crystal grains having a particle size of less than or equal to 0.5 μm is: greater than or equal to 0.1 μm and less than or equal to 0.5 μm.
[0096] In some embodiments, the number of copper grains with a particle size greater than 0.5 μm accounts for 5%-20%, 2%-20%, 2%-15%, 5%-15%, 5%-13%, 6%-12% or 7%-10% of the total number of copper grains, which helps to further improve the elongation at break and optimize the plasticity of the copper foil.
[0097] In some embodiments, the amount of copper grains having a particle size greater than 0.5 μm in the total number of copper grains is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 18%, 20%, 25%, 30%, or a range between any two of the above values or any value within the range.
[0098] Herein, the particle size range of copper grains with a particle size greater than 0.5 μm is: greater than 0.5 μm and less than or equal to 3 μm, which helps to reduce or optimize the average particle size of the copper foil and improve the tensile strength of the copper foil.
[0099] The number percentage and particle size of the grains in the copper foil can be tested by methods known in the art. As an example, the cross-section of the copper foil is measured by electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain an inverse pole figure distribution map with a magnification of 3000. The number and particle size of the grains are counted by imageJ analysis software equipped with Oxford C-Nano+ electron backscatter diffractometer. The equivalent circular diameter of the grain is used as the grain size to make a number distribution map, and the skewed distribution is used for fitting to obtain the grain size and the number percentage of grains in different particle size ranges.
[0100] In some embodiments, the average particle size of the copper grains is 0.3 μm-1.2 μm. In some embodiments, the average particle size of the copper grains is 0.3 μm-0.6 μm. In some embodiments, the average particle size of the copper grains is 0.3 μm-0.5 μm. In some embodiments, the average particle size of the copper grains is 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, or a range between any two of the above values or any value within the range.
[0101] Theoretically, a suitable particle size range is conducive to the copper foil obtaining suitable grain boundaries, which can make the copper foil have suitable resistance to grain dislocation movement and deformation resistance, thereby optimizing the mechanical strength of the copper foil.
[0102] The average particle size of the grains can be tested by methods known in the art. As an example, the cross section of the copper foil is measured by electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain the inverse pole figure distribution map. The number and particle size of the grains are counted by imageJ analysis software supporting Oxford C-Nano+ electron backscatter diffractometer. The equivalent circular diameter of the grains is used as the grain size, and a number distribution map is made. The skewed distribution is used for fitting to obtain the average particle size of the grains.
[0103] In some embodiments, the maximum particle size of the copper grains is 1 μm-2.5 μm. In some embodiments, the maximum particle size of the copper grains is 1.2 μm-1.8 μm or 1.2 μm-2.0 μm. In some embodiments, the maximum particle size of the copper grains is 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or a range between any two of the above values or any value within the range.
[0104] The maximum particle size of the copper grains can be tested by methods known in the art. As an example, the cross section of the copper foil is measured by electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain the inverse polar figure distribution map, and the number and particle size of the grains are counted by the imageJ analysis software supporting the Oxford C-Nano+ electron backscatter diffractometer. The equivalent circle diameter of the grain is used as the grain size, and the number distribution map is made, and the skewed distribution is used for fitting. In the statistical results, the largest grain size is the maximum grain size of the copper grains.
[0105] In some embodiments, the minimum particle size of the copper grains is 0.1 μm-0.3 μm. In some embodiments, the minimum particle size of the copper grains is 0.1 μm-0.3 μm. In some embodiments, the minimum particle size of the copper grains is 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, or a range between any two of the above values or any value within the range.
[0106] The minimum particle size of copper grains can be tested by methods known in the art. As an example, the cross section of copper foil is measured by electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain the inverse pole figure distribution map, and the number and particle size of grains are counted by imageJ analysis software supporting Oxford C-Nano+ electron backscatter diffractometer. The equivalent circle diameter of the grain is used as the grain size, and the number distribution map is made, and the skewed distribution is used for fitting. In the statistical results, the smallest grain size is the minimum grain size of copper grains.
[0107] The particle size span between the maximum particle size and the minimum particle size is the difference between the maximum particle size and the minimum particle size in the particle size distribution of the copper foil grains. In some embodiments, the particle size span of the copper grains is 0.8μm-2.5μm. In some embodiments, the particle size span of the copper grains is 0.8μm-2μm. In some embodiments, the particle size span of the copper grains is 1μm-2μm. In some embodiments, the particle size span of the copper grains is 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.5μm, or a range between any two of the above values or any value within the range.
[0108] The particle size span of the copper grains within the range can make the discrete degree of the copper grain size distribution within an appropriate range, which can help to take into account the grain boundary area and geometric required dislocation density of the copper grains, improve the resistance to grain dislocation movement and reduce the occurrence of concentrated stress during the deformation of the copper foil, which is beneficial for the copper foil to have excellent plasticity while improving mechanical strength.
[0109] In some embodiments, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 600MPa-1000MPa. In some embodiments, the tensile strength of the copper foil is 700MPa-1000MPa. In some embodiments, the tensile strength of the copper foil is 700MPa-800MPa.
[0110] In some embodiments, under the test conditions of room temperature (20±10° C.), sample length×width of (50±0.25 mm)×(15±0.25 mm), and tensile speed of 50±0.5 mm / min, the elongation at break of the copper foil is 4%-8%. In some embodiments, the elongation at break of the copper foil is 4%-7%. In some embodiments, the elongation at break of the copper foil is 5%-6%.
[0111] As used herein, the term "tensile strength" refers to the maximum load-bearing strength per unit area of a specimen when a load is continuously applied to the specimen until it breaks.
[0112] In this article, the term "elongation at break" refers to the ratio of the length change of a material when it undergoes plastic deformation until it breaks after being subjected to force to its original length. It is usually expressed as a percentage and is an important parameter for measuring the deformation ability of a material under stress during stretching.
[0113] In the present application, the tensile strength and elongation at break of the copper foil can be tested by methods known in the art, such as testing according to the GB / T 5230-1995 "Electrolytic Copper Foil" standard. As an example, cut at least 4 specimens with a test area length of 50±0.25mm and a width of 15±0.25mm, and continuously load the specimens at a tensile speed of 50±0.5mm / min at room temperature (20±10°C) until they break, and the maximum load divided by the cross-sectional area of the specimen is used as the tensile strength of the specimen. The cross-sectional area of the specimen can be calculated by dividing the mass of the specimen by the product of the length and density of the specimen. The elongation at break can be calculated according to the displacement method after the above test. The test area refers to the detection area during instrument testing. Considering that the specimen may need to be fixed by a clamp during the test, the length and width of the specimen can be greater than the length and width of the test area.
[0114] In some embodiments, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 600MPa, 650MPa, 700MPa, 750MPa, 800MPa, 850MPa, 900MPa, 950MPa, 1000MPa, or a range between any two of the above values or any value within the range.
[0115] In some embodiments, under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the elongation at break of the copper foil is 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, or a range between any two of the above values or any value within the range.
[0116] The copper foil having the above-mentioned extension strength and elongation at break has excellent mechanical strength and plasticity, can be applied to high energy density batteries or high expansion batteries, and helps to improve the safety of secondary batteries.
[0117] In some embodiments, the hardness of the copper foil is 55HV-65HV. In some embodiments, the hardness of the copper foil is 55HV-60HV. In some embodiments, the hardness of the copper foil is 55HV, 56HV, 57HV, 58HV, 59HV, 60HV, 61HV, 62HV, 63HV, 64HV, 65HV, or a range between any two of the above values or any value within the range.
[0118] Hardness can reflect the compressive deformation or puncture resistance of copper foil. In the preparation process of secondary batteries, the surface quality of copper foil can affect the bonding performance between the negative electrode film layer and copper foil, especially in the cold pressing step of secondary batteries, the negative electrode active material particles press the copper foil under external pressure. Appropriate hardness is conducive to reducing surface damage of copper foil and reducing the impact on the bonding performance between the negative electrode film layer and copper foil.
[0119] In some embodiments, the copper foil has a thickness of 4 μm-10 μm. In some embodiments, the copper foil has a thickness of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range between any two of the above values or any value within the range.
[0120] In this application, the thickness of the copper foil can be tested by a method known in the art. As an example, a 20×15 cm 2 The cut sample is placed on an electronic balance for weighing to obtain the sample weight. According to the density of copper foil, ρ is 8.96 g / cm 3 Calculate the volume of the spline. Given the length and width of the spline, the thickness of the spline can be calculated.
[0121] The maximum load that ordinary strength copper foil can carry after thinning is sharply reduced, and the thickness of copper foil that can be used for plastic deformation is severely reduced, resulting in a significant decrease in the tensile strength and elongation at break of the copper foil. Fatigue fracture is prone to occur in the later stage of the secondary battery cycle, causing safety accidents. The copper foil provided in this application still has excellent tensile strength and elongation at break within a thickness range of 4μm-10μm, and has good mechanical properties and plasticity. The copper foil can be thinned without affecting strength, which helps in lightweight design of batteries, helps reduce battery weight and further improves the energy density or specific capacity of secondary batteries.
[0122] The secondary battery provided in the present application can be prepared by a method comprising the following steps: preparing copper foil by electroplating, the electroplating method comprising applying a pulse current to a plating solution to reduce and deposit copper ions in the plating solution to form copper foil, the peak value of the pulse current is 40000A-100000A, the valley value of the pulse current is 100A-20000A, and the current variation period is 50ms-5000ms.
[0123] In this article, the term "electroplating method" refers to a method of depositing metal or alloy on the surface of a workpiece to form a metal layer using the principle of electroplating.
[0124] As used herein, the term "pulsed current" refers to current or voltage pulses that occur repeatedly in a cycle.
[0125] Compared with the calendering method in the prior art, the electroplating process is mature and simple, has low equipment requirements and low manufacturing cost. The prepared copper foil has excellent tensile strength and elongation at break. It not only has excellent mechanical strength and plasticity, but also helps to reduce the manufacturing cost of secondary batteries.
[0126] Some solutions use high direct current to prepare copper foil by electroplating in order to improve the mechanical strength of copper foil. However, due to the small difference in work hardening ability between grains, the ability to suppress strain localization is reduced, and concentrated stress is very likely to occur in the copper foil during deformation, and the plasticity of the copper foil is reduced, which is very likely to cause brittle fracture risk. The preparation method provided by the present application uses a pulse current to adjust the nucleation and growth rate of copper grains by continuously changing the current, thereby adjusting the size and morphology of the copper grains, as well as adjusting the number ratio of copper grains with a particle size of less than or equal to 0.5 μm and copper grains with a particle size greater than 0.5 μm, and improving the tensile strength and elongation at break of the copper foil, so that the copper foil has both excellent mechanical properties and plasticity.
[0127] In some embodiments, the peak value of the pulse current is 40000A-80000A. In some embodiments, the peak value of the pulse current is 50000A-70000A. In some embodiments, the peak value of the pulse current is 55000A-70000A, 50000A-80000A, 55000A-80000A, 50000A-60000A.
[0128] In some embodiments, the peak value of the pulse current is 45000A, 50000A, 55000A, 60000A, 65000A, 70000A, 75000A, 80000A, 85000A, 90000A, 95000A, 100000A, or a range between any two of the above values or any value between the ranges.
[0129] In some embodiments, the valley value of the pulse current is 1000A-10000A. In some embodiments, the valley value of the pulse current is 2000A-5500A. In some embodiments, the valley value of the pulse current is 2500A-5000A, 2000A-8000A, or 2000A-5000A.
[0130] In some embodiments, the valley value of the pulse current is 100A, 500A, 1000A, 1500A, 2000A, 2500A, 3500A, 4000A, 4500A, 5000A, 8000A, 10000A, 15000A, 20000A, or a range between any two of the above values or any value between the ranges.
[0131] In some embodiments, the variation period of the pulse current is 500ms-5000ms. In some embodiments, the variation period of the pulse current is 2000ms-4000ms. In some embodiments, the variation period of the pulse current is 50ms, 100ms, 200ms, 500ms, 1000ms, 1200ms, 1500ms, 1800ms, 2000ms, 2500ms, 2750ms, 3000ms, 3500ms, 4000ms, 4500ms, 5000ms, or a range between any two of the above values or any value between the ranges.
[0132] Herein, the term "peak value" refers to the maximum current value of a pulse current, usually the value at the crest of a pulse current waveform. Similarly, the term "valley value" refers to the minimum current value of a pulse current, usually the value at the trough of a pulse current waveform.
[0133] Herein, the term “variation period” refers to the time between two adjacent peaks or troughs in a pulse current waveform, and the unit is ms.
[0134] During the copper ion deposition process, increasing the current can speed up the copper ion deposition rate, which helps to form fine grains with smaller particle sizes; reducing the current can reduce the copper ion deposition rate, which helps to form relatively regular and orderly large particle size grains, such as columnar crystals. Adjusting the current variation parameters, namely the peak value, valley value and variation cycle, helps to adjust the formation of copper grain nuclei, the growth rate of grains and the deposition time of copper ions, producing a heterogeneous grain morphology with mixed distribution of large and small grains, and adjusting the particle size and number ratio of grains, thereby improving the tensile strength and elongation at break of copper foil, so that copper foil has both excellent mechanical strength and plasticity.
[0135] In some embodiments, the pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current.
[0136] In some embodiments, the pulse current includes a sinusoidal pulse current. The sinusoidal pulse current changes continuously and periodically, which is conducive to the continuous and variable growth of the grains.
[0137] In some embodiments, the preparation method is a continuous production method.
[0138] In some embodiments, the preparation method is a roller deposition method. Its working principle is that the cathode roller is connected to the negative pole of the power supply, and the anode tank is connected to the positive pole of the power supply. When the electroplating solution containing copper ions enters the anode tank, an electric field is formed between the positive and negative electrodes. Under the action of the electric field, the copper ions migrate and deposit on the surface of the cathode roller, and the deposited copper foil is peeled off from the cathode roller and rolled on another roller. The electroplating solution is continuously added and circulated, and the copper ions are continuously deposited on the cathode roller under the action of the electric field, continuously peeled off and rolled on the winding shaft. This preparation method can realize the continuous production of large-scale copper foil, providing the possibility for industrial application.
[0139] In some embodiments, the cathode electrode is a titanium roller or plate.
[0140] In some embodiments, the anode electrode is a titanium substrate plate.
[0141] In some embodiments, the spacing between the cathode electrode and the anode electrode is 8 mm to 20 mm. In some embodiments, the spacing between the cathode electrode and the anode electrode is 8 mm to 12 mm. In some embodiments, the spacing between the cathode electrode and the anode electrode is 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or a range between any two of the above values or any value between the ranges.
[0142] In some embodiments, the temperature of the electroplating deposition is 45° C.-60° C. In some embodiments, the temperature of the electroplating deposition is 50° C.-60° C. In some embodiments, the deposition temperature can be 45° C., 50° C., 55° C., 60° C., a range between any two of the above values, or any value in the range.
[0143] In some embodiments, the roller speed of the cathode roller is 2 m / min-5 m / min. In some embodiments, the roller speed of the cathode roller is 2 m / min-3 m / min. In some embodiments, the roller speed of the cathode roller is 2 m / min, 2.5 m / min, 3 m / min, 3.5 m / min, 4 m / min, 4.5 m / min, 5 m / min, or a range between any two of the above values or any value between the ranges.
[0144] The cathode roller can be any roller suitable for preparing copper foil in the art, for example, a titanium roller.
[0145] In some embodiments, the electroplating solution includes a leveler, a wetting agent, and a brightener.
[0146] In this article, the term "leveler" refers to a substance added to the electroplating solution to improve the flatness of the coating. It can adhere to the tip of the copper foil with a fast deposition rate, inhibit grain growth, balance the growth rate of pits and tips, and improve the flatness of the copper foil.
[0147] In this article, the term "wetting agent" refers to a substance used to reduce the interfacial tension between the plating solution / electrode and to make the coating adhere better to the substrate. The wetting agent can improve the wettability of the plating solution and the substrate. The wettability of the plating solution on the cathode is sufficient to enable rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and reduce the grain size in the copper foil.
[0148] In this article, the term "brightener" refers to a substance that improves the smoothness of the coating and reduces the surface roughness. Brightener can make the grain size of copper foil smaller, reduce the surface roughness of copper foil, and improve the smoothness of the surface.
[0149] In some embodiments, the leveler comprises one or more of collagen and sodium saccharin. In some embodiments, the leveler comprises collagen and sodium saccharin.
[0150] Without being bound by any theory, collagen can inhibit the deposition of copper ions and balance the growth rate of pits and tips. The introduction of sodium saccharin can attract copper ions to deposit in the depressions on the surface of the copper foil, reduce the microscopic defects or unevenness inside the copper foil, and reduce the warpage defects caused by these defects. Two different leveling agents help to further improve the surface pits and protrusions of the copper foil and improve the flatness of the copper foil.
[0151] In some embodiments, the concentration of the collagen in the plating solution is 60 mg / L to 300 mg / L. In some embodiments, the concentration of the collagen in the plating solution is 80 mg / L-150 mg / L. In some embodiments, the concentration of the collagen in the plating solution is 60 mg / L, 80 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, or a range between any two of the above values or any value within the range.
[0152] The collagen may be selected from proteins with a molecular weight commonly used in the copper foil field, for example, collagen with a relative molecular weight of 8000-12000.
[0153] In some embodiments, the concentration of saccharin sodium in the electroplating solution is 0.5 g / L-10 g / L. In some embodiments, the concentration of saccharin sodium in the electroplating solution is 0.5 g / L-4 g / L. In some embodiments, the concentration of saccharin sodium in the electroplating solution is 0.5 g / L, 0.8 g / L, 1 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L, 6.0 g / L, 6.5 g / L, 7.0 g / L, 7.5 g / L, 8.0 g / L, 8.5 g / L, 9.0 g / L, 9.5 g / L, 10 g / L, or a range between any two of the above values or any value between the ranges. In some embodiments, the wetting agent comprises one or more of hydroxyethyl cellulose, polyethylene glycol, etc. In some embodiments, the wetting agent comprises hydroxyethyl cellulose and polyethylene glycol.
[0154] Without being bound by any theory, hydroxyethyl cellulose has good water solubility and thickening properties, can form a uniform solution in water, increase the viscosity of the plating solution and adhere to the surface of the copper foil substrate. Polyethylene glycol, as a lubricant and wetting agent, can reduce the surface tension of the liquid and enhance the wetting ability of the liquid on the solid surface. The combined use of the two can improve the adhesion of the plating solution, improve and assist the copper ions to adhere to the substrate surface and deposition, improve the consistency of the grains during the deposition process, reduce the difference in grain size in the thickness direction, improve the uniformity of the copper foil, and thus improve the mechanical properties of the copper foil.
[0155] In some embodiments, the concentration of the polyethylene glycol in the plating solution is 50 mg / L to 200 mg / L. In some embodiments, the concentration of the polyethylene glycol in the plating solution is 60 mg / L to 150 mg / L. In some embodiments, the concentration of the polyethylene glycol in the plating solution is 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, or a range between any two of the above values or any value within the range.
[0156] The polyethylene glycol may have a molecular weight commonly used in the copper foil field, for example, polyethylene glycol with a relative molecular weight of 4000.
[0157] In some embodiments, the concentration of the hydroxyethyl cellulose in the plating solution is 30 mg / L to 200 mg / L. In some embodiments, the concentration of the hydroxyethyl cellulose in the plating solution is 50 mg / L-150 mg / L. In some embodiments, the concentration of the hydroxyethyl cellulose in the plating solution is 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 120 mg / L, 140 mg / L, 160 mg / L, 180 mg / L, 200 mg / L, or a range between any two of the above values or any value between the ranges.
[0158] The polyethylene glycol may have a molecular weight commonly used in the copper foil field. In some embodiments, the relative molecular mass of the hydroxyethyl cellulose is 120,000.
[0159] In some embodiments, in the electroplating solution, the mass ratio of the polyethylene glycol to the hydroxyethyl cellulose is (1-1.5): 1. In some embodiments, in the electroplating solution, the mass ratio of the polyethylene glycol to the hydroxyethyl cellulose is (1.2-1.5): 1. As an example, the mass ratio of the polyethylene glycol to the hydroxyethyl cellulose is 1: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1, or a range between any two of the above values or any value within the range.
[0160] In some embodiments, the brightener includes sodium poly(dipropylene glycol disulfide) sulfonate.
[0161] Without being bound by any theory, sodium polydipropylene sulfonate is adsorbed on the cathode copper surface through thiol functional groups or disulfide bonds. The terminal sulfonate anions capture the hydrated copper ions in the electroplating solution, thereby destroying their hydration, and interact with the chloride ions adsorbed on the cathode surface, so that electrons are transferred to the captured copper ions through the chloride ions, thereby greatly improving the electrochemical reduction rate of copper ions, refining the grains and achieving material strengthening.
[0162] In some embodiments, the concentration of the sodium polydipropane disulfide sulfonate in the electroplating solution is 500 mg / L to 2000 mg / L. In some embodiments, the concentration of the sodium polydipropane disulfide sulfonate in the electroplating solution is 500 to 1000 mg / L. In some embodiments, the concentration of the sodium polydipropane disulfide sulfonate in the electroplating solution is 500 mg / L, 600 mg / L, 700 mg / L, 800 mg / L, 900 mg / L, 1000 mg / L, 1500 mg / L, 2000 mg / L, or a range between any two of the above values or any value between the ranges.
[0163] In some embodiments, the electroplating solution includes chloride ions, and the concentration of the chloride ions (in terms of chlorine atoms) is 20 mg / L to 80 mg / L. In some embodiments, the concentration of the polydisulfide propane sulfonate sodium in the electroplating solution is 40 mg / L to 80 mg / L. In some embodiments, the concentration of the chloride ions (in terms of chlorine atoms) is 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, or a range between any two of the above values or any value between the ranges. The use of chloride ions in combination with a wetting agent can further improve the electrodeposition process.
[0164] In some embodiments, the electroplating solution includes: collagen with a concentration of 60 mg / L to 300 mg / L, saccharin sodium with a concentration of 0.5 g / L-10 g / L, polyethylene glycol with a concentration of 50 to 200 mg / L, hydroxyethyl cellulose with a concentration of 30 mg / L to 200 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 500 mg / L to 2000 mg / L, and chloride ions with a concentration of 20 mg / L to 80 mg / L.
[0165] In some embodiments, the electroplating solution includes: collagen with a concentration of 80 mg / L to 150 mg / L, saccharin sodium with a concentration of 0.5 g / L-4 g / L, polyethylene glycol with a concentration of 60 mg / L to 150 mg / L, hydroxyethyl cellulose with a concentration of 50 mg / L to 150 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 500 mg / L to 1000 mg / L, and chloride ions with a concentration of 40 mg / L to 80 mg / L.
[0166] The electroplating solution also includes a copper source to provide copper ions to the electroplating solution. The electroplating solution also includes sulfuric acid to provide an acidic environment for the reduction of copper ions.
[0167] In some embodiments, the concentration of the copper ions (calculated as copper atoms) is 60 g / L to 100 g / L. In some embodiments, the concentration of the copper ions (calculated as copper atoms) is 80 g / L to 100 g / L. In some embodiments, the concentration of the copper ions (calculated as copper atoms) is 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, any range between any two of the above values, or any value between the ranges.
[0168] In some embodiments, the concentration of the sulfuric acid is 60 g / L to 110 g / L. In some embodiments, the concentration of the sulfuric acid is 80 g / L to 110 g / L. In some embodiments, the concentration of the sulfuric acid is 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, any range between any two of the above values, or any value within the range.
[0169] In some embodiments, the pH of the electroplating solution is 2.5-4.5, such as 2.5, 3.0, 3.5, 4.0, 4.5, or a range between any two of the above values or any value between the ranges.
[0170] The synergistic effect of the electroplating solution and the electroplating parameters helps to form a copper foil with heterogeneous grain morphology with different grain sizes, and the copper foil has excellent tensile strength and elongation at break, which is beneficial to improving the safety performance of high energy density or high expansion batteries. At the same time, the preparation method can achieve large-scale manufacturing and has the prospect of industrial application.
[0171] [Negative electrode]
[0172] As an example of a negative electrode sheet, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0173] In some embodiments, the negative electrode current collector may be the current collector described in the first aspect of the present application, thereby providing a material basis for improving the energy density of the secondary battery and helping to improve the safety of the secondary battery.
[0174] In some embodiments, the other negative electrode active materials include, but are not limited to, one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The tin-based materials may include one or more of elemental tin, tin oxide, and tin alloy materials.
[0175] In some embodiments, the negative electrode active material includes a silicon-based material, and the silicon-based material includes one or more of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy material.
[0176] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0177] In some embodiments, the negative electrode plate further includes a conductive agent, which includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0178] In some embodiments, the conductive agent includes carbon black. In some embodiments, the conductive agent includes carbon nanotubes. In some embodiments, the conductive agent includes carbon black and carbon nanotubes. The conductive agent has a wide range of sources and excellent conductivity, which is beneficial to controlling the preparation cost of the secondary battery and improving the conductivity of the negative electrode sheet.
[0179] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0180] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0181] [Positive electrode]
[0182] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0183] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0184] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0185] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0186] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0187] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0188] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0189] [Electrolytes]
[0190] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0191] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0192] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0193] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0194] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0195] [Isolation film]
[0196] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0197] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0198] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0199] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0200] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0201] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0202] In one embodiment of the present application, a secondary battery is provided.
[0203] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0204] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0205] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0206] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0207] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0208] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0209] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0210] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0211] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0212] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0213] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0214] Example
[0215] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0216] 1. Performance Testing
[0217] (1) Grain characteristic test of copper foil
[0218] Electron backscatter diffraction (EBSD) combined with scanning electron microscopy was used to observe the cross section of the copper foil, where the electron backscatter diffractometer model was Oxford C-Nano+. The inverse pole figure distribution map (magnification 3000) was obtained, the particle size of each grain was measured, the diameter of the equivalent circle of the grain was used as the particle size of the grain, and the distribution statistics of the grain size were performed. The skewed distribution was used for fitting to obtain the total number of copper grains, average particle size, maximum particle size, minimum particle size, particle size span, the number of copper grains with a particle size less than or equal to 0.5μm, and the number of copper grains with a particle size greater than 0.5μm.
[0219] (2) Mechanical properties test
[0220] According to GB / T 5230-1995 "Electrolytic Copper Foil", the copper foil obtained by cutting the embodiment is a tensile specimen with a length L0 of 50 mm and a width of 15 mm. The tensile properties are tested at 25° C. using a universal testing machine, and the tensile rate is set to 50 mm / min.
[0221] The cross-sectional area of the stretched spline is Where ρ is 8.96 g / cm 3 , m is in grams, and L0 is in centimeters.
[0222] Continuously apply load to the sample until it breaks, read the maximum load F from the force gauge or tensile curve, and calculate the tensile strength σ according to formula I b .
[0223]
[0224] The distance between the two lines after the sample is broken is L1, which can be measured on the sample or read from the tensile curve. L1 can be measured by the straight line method or the displacement method, and the elongation at break δ can be calculated according to formula II.
[0225]
[0226] (3) Hardness test
[0227] Place the copper foil sample in a metallographic hot mounting machine, pour in wood glue powder and heat at a rate of 150°C / 10min. Use a Vickers hardness tester with a prismatic indenter to press into the copper foil sample (50g weight), optically measure the length of the two diagonals, and obtain the corresponding Vickers hardness according to the following Vickers hardness calculation formula.
[0228]
[0229] HV stands for Vickers hardness;
[0230] F represents the load of the indenter (Newton force);
[0231] α represents the relative angle between the indenters (136°);
[0232] d is the average length of the diagonal lines (mm).
[0233] (4) State of Health (SOH) corresponding to crack failure
[0234] At 25°C, the battery is charged at 1C constant current to a voltage of 3.8V, then charged at 3.8V constant voltage to a current ≤ 0.05C, and then discharged at 1C constant current to a voltage of 2.5V. This is a charge and discharge process, and the charge and discharge cycle is repeated. The battery SOH is monitored throughout the process, and then the battery electronic computer tomography (CT) is performed every 1% SOH to determine whether cracks occur inside the battery. If cracks occur, the battery that fails during the cycle will be disassembled to observe whether the negative electrode of the battery is broken, and the SOH corresponding to the crack failure is obtained.
[0235] 2. Preparation method
[0236] Example 1
[0237] (1) Preparation of copper foil
[0238] A copper plate or copper wire with a purity of more than 99.9% is dissolved in sulfuric acid with a mass content of 98% to obtain a copper sulfate solution, which is used as a copper source, and an additive and hydrochloric acid are added at 55°C to prepare an electroplating solution. Among them, the concentration of collagen (relative molecular weight of 8000-12000) is 120 mg / L, the concentration of polyethylene glycol (relative molecular weight of 4000) is 80 mg / L, the concentration of hydroxyethyl cellulose (relative molecular weight of about 120000) is 60 mg / L, the concentration of chloride ions is 40 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 600 mg / L, the concentration of sodium saccharin is 2 g / L, the concentration of copper ions (in terms of copper atoms) is 90 g / L, and the rest is deionized water. The pH of the electroplating solution is 3.5.
[0239] The sine wave pulse current is used to apply the current periodically to the polished cathode titanium roller, and the anode electrode is the titanium substrate plate. The area of the titanium roller in the electroplating solution is 8.67m 2 The rotation speed (roller speed) of the titanium roller is 2.4m / min, and a sinusoidal pulse current is applied, with a peak current of 55000A, a peak-to-valley current of 2500A, a period of 3000ms, a cathode-anode distance of 10mm, and a deposition temperature of 55°C. Copper foil is deposited on the titanium roller with a thickness of 6μm.
[0240] (2) Preparation of batteries
[0241] The positive electrode active material LiNi 0.8 Co 0.1Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are dissolved in solvent N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and the positive electrode slurry is obtained after being fully stirred and mixed. Thereafter, the positive electrode slurry is evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain the positive electrode sheet.
[0242] The negative electrode active material silicon carbon (silicon content 20wt%-50wt%), artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in solvent deionized water at a weight ratio of 20:76:1:1.5:1.5, and are evenly mixed to prepare a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode collector copper foil once or multiple times, and a negative electrode film is obtained after drying, and then a negative electrode pole piece is obtained by cold pressing and slitting.
[0243] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), ethylene carbonate, diethyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was dissolved in the above solution to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 was 1 mol / L. Then, 2.0wt% of fluoroethylene carbonate, 0.5wt% of 1,3-propane sultone, and 0.5wt% of succinic anhydride were added to the above organic solvent as additives, and the mixture was mixed and stirred to obtain an electrolyte.
[0244] Polypropylene film is used as the isolation film.
[0245] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in a battery casing, and after drying, the electrolyte is injected, and then a lithium-ion battery is obtained through processes such as formation and standing.
[0246] Example 2-3
[0247] The preparation method of Example 2-3 is basically the same as that of Example 1, but the composition of the electroplating solution (see Table 1) and the parameters of the sinusoidal pulse current (see Table 2) are adjusted; the thickness of the deposited copper foil is 6 μm.
[0248] Comparative Example 1-2
[0249] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, but a direct current is used for deposition, and the deposition current is 55000 A. The thickness of the copper foil is 6 μm.
[0250] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, using a DC deposition current of 30000 A. The thickness of the copper foil is 6 μm.
[0251] Table 1: Plating solution components
[0252]
[0253] Table 2: Sine wave pulse current parameters
[0254]
[0255] NA means not applicable.
[0256] The grain characteristics and mechanical characteristics of the copper foils prepared in Examples 1-3 and Comparative Examples 1-2, as well as the results of the secondary batteries are shown in Table 3 below.
[0257] Table 3
[0258]
[0259]
[0260] Figure 7 , Fig.10 and Fig.13 The inverse pole figure distribution diagrams of the copper foil cross sections of Examples 1-3 after EBSD testing are shown respectively. The copper foil cross sections present a heterogeneous grain structure with large and small grains doped and distributed. Compared with the inverse pole figure distribution diagram of the copper foil of Comparative Example 2 ( Fig.17 ) It can be seen from the comparison that there are more fine grains distributed in the copper foil of Examples 1-3, and the grain size is smaller overall.
[0261] Fig. 9 , Fig.12 , Fig.15 and Fig.19 The particle size distribution diagrams of the copper foils of Examples 1-3 and Comparative Example 2 are shown respectively. Combined with Table 3, it can be seen that in the copper foils of Examples 1-3, the number of copper grains with a particle size less than or equal to 0.5 μm accounts for between 70% and 95%, and is concentrated in the range of 80%-95%, while the number of copper grains with a particle size less than or equal to 0.5 μm in Comparative Example 2 accounts for less than 50%, indicating that the copper grains of Examples 1-3 are finer as a whole, and the copper foil has higher mechanical strength. In addition, in the copper foils of Examples 1-3, the number of copper grains with a particle size greater than 0.5 μm accounts for 5%-30%, while the number of copper grains with a particle size greater than 0.5 μm in Comparative Example 2 accounts for 50.5%, and the copper foils of Examples 1-3 have plasticity that is basically equivalent to that of the copper foil of Comparative Example 2. This shows that the preparation of copper foil by sinusoidal pulse current helps to adjust the particle size distribution of copper grains, thereby improving the mechanical properties and plasticity of the copper foil.
[0262] In the copper foils of Examples 1-3, the average particle size is in the range of 0.3μm-0.6μm, the maximum particle size is in the range of 1μm-2μm, the minimum particle size is in the range of 0.1μm-0.3μm, and the particle size span is 0.8μm-2μm. In Comparative Example 2, the span of the copper grain size is larger and the average copper grain size is larger. It can be understood that the copper foils of Examples 1-3 have more accumulated crystal interface density and greater mechanical strength; the copper foil of Comparative Example 2 has less accumulated crystal interface density and lower mechanical strength. This also corresponds to the tensile strength of Examples 1-3 and Comparative Example 2.
[0263] Figure 8 , Fig.11 and Fig.14 The tensile curves of the copper foils of Examples 1-3 are shown respectively. It can be seen that the tensile strength of the prepared copper foil is in the range of 600MPa-1000MPa, and the elongation at break of the copper foil is in the range of 4%-8% (Table 3), indicating that the copper foil has excellent strength and plasticity. Fig.16 The tensile curve of the copper foil of Comparative Example 1 is shown. The tensile strength of the copper foil is similar to that of Example 1, but the elongation at break is only 2.7%, indicating poor plasticity. Fig.18 The tensile curve of the copper foil of Comparative Example 1 is shown. The elongation at break of the copper foil is similar to that of Example 1, but the tensile strength is poor.
[0264] The hardness of the copper foils of Examples 1 to 3 is in the range of 55 HV to 65 HV, indicating that the copper foils have good compressive deformation or puncture resistance capabilities.
[0265] Comparative Example 1 uses a direct current with the same peak current as that of Example 1 to prepare a copper foil. Compared with Example 1, it can be seen that the copper foil of Comparative Example 1 has similar tensile strength and hardness as the copper foil of Example 1, but the elongation at break is significantly lower than that of Example 1. This shows that the particle size distribution of copper grains can be adjusted by the sinusoidal pulse current and current parameters, so that the copper foil has excellent plasticity while having good mechanical strength.
[0266] Compared with Comparative Examples 1-2, the SOH corresponding to the crack failure of Examples 1-3 is significantly reduced, which shows that the copper foil prepared in Examples 1-3 significantly improves the service life of the secondary battery and improves the safety of the secondary battery. Although the copper foil of Comparative Example 2 has excellent elongation at break, its tensile strength is low, resulting in a relatively high SOH value corresponding to the crack failure. Relatively speaking, the tensile strength of the copper foil prepared in Examples 1-3 using a sinusoidal pulse current with varying current size is significantly improved, and good plasticity is maintained, and the SOH value corresponding to the crack failure is significantly reduced, which can improve the service life of the battery cell by more than 25% SOH.
[0267] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, characterized in that: The invention comprises copper foil, wherein the copper foil comprises copper grains of different particle sizes, wherein the copper grains comprise copper grains with a particle size of less than or equal to 0.5 μm and copper grains with a particle size of greater than 0.5 μm, wherein the number of copper grains with a particle size of less than or equal to 0.5 μm accounts for 70%-95% of the total number of copper grains, and the number of copper grains with a particle size of greater than 0.5 μm accounts for 5%-30% of the total number of copper grains.
2. The secondary battery according to claim 1, characterized in that: The particle size range of the copper crystal grains with a particle size greater than 0.5 μm is: greater than 0.5 μm and less than or equal to 3 μm.
3. The secondary battery according to claim 1 or 2, characterized in that: The number of copper crystal grains with a particle size of less than or equal to 0.5 μm accounts for 80%-95% of the total number of copper crystal grains, and / or the number of copper crystal grains with a particle size of greater than 0.5 μm accounts for 5%-20% of the total number of copper crystal grains.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The copper foil satisfies at least one of the following conditions: (1) The average particle size of copper grains is 0.3 μm-1.2 μm; (2) The maximum particle size of copper grains is 1 μm-2.5 μm; (3) The minimum particle size of copper grains is 0.1 μm-0.3 μm; (4) The particle size of copper grains ranges from 0.8 μm to 2.5 μm.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The copper foil satisfies at least one of the following conditions: (1) The average particle size of copper grains is 0.3 μm-0.6 μm; (2) The maximum particle size of copper grains is 1.2 μm-2.0 μm; (3) The minimum particle size of copper grains is 0.1 μm-0.3 μm; (4) The particle size of copper grains ranges from 1 μm to 2 μm.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: Under the test conditions of room temperature (20±10°C), sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the tensile strength of the copper foil is 600MPa-1000MPa, and / or the elongation at break of the copper foil is 4%-8%.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: Under the test conditions of room temperature (20±10° C.), sample length×width of (50±0.25 mm)×(15±0.25 mm), and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is 700 MPa-1000 MPa, and / or the elongation at break of the copper foil is 4%-7%.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: Under the test conditions of room temperature (20±10° C.), sample length×width of (50±0.25 mm)×(15±0.25 mm), and tensile speed of 50±0.5 mm / min, the tensile strength of the copper foil is 700 MPa-800 MPa, and / or the elongation at break of the copper foil is 5%-6%.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The hardness of the copper foil is 55HV-65HV.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The hardness of the copper foil is 55HV-60HV.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The copper foil has a thickness of 4 μm-10 μm.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The secondary battery also includes a negative electrode film layer located on at least one side of the copper foil, and the negative electrode active material in the negative electrode film layer includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material and lithium titanate.
13. The secondary battery according to claim 12, characterized in that: The negative electrode active material includes a silicon-based material, and the silicon-based material includes at least one of elemental silicon, a silicon-oxygen compound, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy.
14. A method for preparing a secondary battery, characterized in that: The invention comprises an electroplating method for preparing copper foil, wherein the electroplating method comprises applying a periodic pulse current to a plating solution to reduce and deposit copper ions in the plating solution to form copper foil; the peak value of the pulse current is 40000A-100000A, the valley value of the pulse current is 100A-20000A, and the variation period of the current is 50ms-5000ms.
15. The preparation method according to claim 14, characterized in that: The electroplating method satisfies one or more of the following conditions: (1) The peak value of the pulse current is 40000A-80000A; (2) The valley value of the pulse current is 1000A-10000A; (3) The pulse current has a variation period of 500ms-5000ms; (4) The distance between the cathode electrode and the anode electrode is 8 mm to 20 mm; (5) The temperature of electroplating deposition is 45°C-60°C; (6) The cathode roller speed is 2m / min-5m / min.
16. The preparation method according to claim 14 or 15, characterized in that: The electroplating method satisfies one or more of the following conditions: (1) The peak value of the pulse current is 50000A-70000A; (2) The valley value of the pulse current is 2000A-5500A; (3) The pulse current has a variation period of 2000ms-4000ms; (4) The distance between the cathode electrode and the anode electrode is 8mm-12mm; (5) The temperature of electroplating deposition is 50℃-60℃; (6) The cathode roller speed is 2m / min-3m / min.
17. The preparation method according to any one of claims 14 to 16, characterized in that: The pulse current includes one or more of a square wave pulse current, a sine wave pulse current, a triangle wave pulse current, and a sawtooth wave pulse current. Optionally, the pulse current includes a sine wave pulse current.
18. The preparation method according to any one of claims 14 to 17, characterized in that: The electroplating solution includes a leveler, a wetting agent and a brightener, The leveling agent includes one or more of collagen and saccharin sodium; The wetting agent includes one or more of hydroxyethyl cellulose and polyethylene glycol; The brightener includes sodium polydipropylene sulfonate.
19. The preparation method according to claim 18, characterized in that: The electroplating solution comprises: collagen with a concentration of 60 mg / L to 300 mg / L, saccharin sodium with a concentration of 0.5 g / L-10 g / L, polyethylene glycol with a concentration of 50 mg / L to 200 mg / L, hydroxyethyl cellulose with a concentration of 30 mg / L to 200 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 500 mg / L to 2000 mg / L, and chloride ions (calculated as chlorine atoms) with a concentration of 20 mg / L to 80 mg / L.
20. The preparation method according to claim 18 or 19, characterized in that: The electroplating solution includes: the electroplating solution includes: collagen with a concentration of 80 mg / L to 150 mg / L, saccharin sodium with a concentration of 0.5 g / L-4 g / L, polyethylene glycol with a concentration of 60 mg / L to 150 mg / L, hydroxyethyl cellulose with a concentration of 50 mg / L to 150 mg / L, sodium polydisulfide dipropane sulfonate with a concentration of 500 mg / L to 1000 mg / L, and chloride ions with a concentration of 40 mg / L to 80 mg / L.
21. The preparation method according to any one of claims 14 to 20, characterized in that: The pH of the electroplating solution is 2.5-4.
5.
22. An electrical device, characterized in that: The invention comprises the secondary battery according to claim 1 to 13 or the secondary battery prepared by the preparation method according to claim 14 to 21.
Citation Information
Patent Citations
Surface treatment method for copper foil, surface treated copper foil and copper foil for negative electrode collector of lithium ion secondary battery
CN102884660A
Filler composition and application thereof
CN104558689A
Surface-treated copper foil, copper-cladded laminate plate, and printed wiring board
CN112004964A
High-extensibility electrolytic copper foil and preparation method thereof
CN113621999A
High-tensile-strength copper foil and preparation method thereof
CN114808046A
Cited By
Secondary battery and preparation method therefor, and electric device
WO2026041071A1
Secondary battery and preparation method therefor, electrode sheet, secondary battery, and electric device
WO2026041161A1
Secondary battery and preparation method therefor, electrode sheet, wound-type secondary battery, and electric device
WO2026041162A1
Secondary battery and preparation method therefor, and electric device
WO2026041165A1
Secondary battery and preparation method therefor, and electric device
WO2026041166A1